Complement-dependent antiviral monospecific antibody-mediated lysis of murine cells coated with Sendai virus or its envelope component. - Hosaka, Y (1980)
Complement-dependent antiviral antibody-mediated lysis of murine cells coated with Sendai virus or its envelope component (P815 mastocytoma cells and L929 cells) was studied with antiviral monospecific sera (anti-F and anti-HN sera). Three types of interactions different in terms of susceptibility of complement-dependent antibody-mediated lysis were distinguished: (i) fusion-positive Sendai viruses induced the susceptibility with both anti-F and anti-HN sera; (ii) fusion-negative envelope particles with F protein induced the susceptibility with only anti-F serum; (iii) noninfectious Sendai viruses with F0 protein induced no susceptibility. The lack of complement-dependent antibody-mediated cytolysis susceptibility in case (iii) was found to be due neither to detachment of cell-associated noninfectious virus in the presence of antiserum nor to antibody-mediated particular redistribution of cell surface virus antigens. Differences in virus or envelope component-cell association in these three cases were discussed.